2023
DOI: 10.4236/ce.2023.142019
|View full text |Cite
|
Sign up to set email alerts
|

Translanguaging as EFL Teaching Method

Abstract: There has been a heated debate about which method of the two, monolingual or bilingual, is more effective in ESL classrooms. As societal demands are shifting upon learning foreign languages, new approaches to second language teaching are rejecting the monolingual norm and long-standing views about acquiring L2 are challenged. The article offers an overview of the literature on this issue and this overview serves as the basis for an updated framework that indicates necessary areas of change in conceptualization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
(56 reference statements)
0
0
0
Order By: Relevance
“…Then, in its turn, the writing reflection involves not only English writing skills but other thinking/reasoning ones, that is, CT-based act categories (3) and ( 4). This L1-L2 transcending approach is firmly backed up by past research reporting that translanguaging was supportively manipulated in the manifestation of L1 language input as reading and discussing while processing L2 language output as writing, which moved students to transcend and go beyond the two languages in a critical and creative process (Baker, 2011;Bolkvadze, 2023;Cenoz & Gorter, 2022;Garcia, 2009;Treffers-Daller et al, 2020;Wei, 2011;Yüzlü, & Dikilitaş, 2022a). As Yüzlü and Dikilitaş (2022b) observed that "Translanguaging can serve different purposesmaking meaning, facilitating learning, promoting communicative abilities" (p.186) supported by the assumption that "the boundaries between languages are soft and fluent and that students should benefit from being multilingual by using resources from their whole linguistic repertoire" (Cenoz & Gorter, 2022, p.344).…”
Section: Methodsmentioning
confidence: 96%
“…Then, in its turn, the writing reflection involves not only English writing skills but other thinking/reasoning ones, that is, CT-based act categories (3) and ( 4). This L1-L2 transcending approach is firmly backed up by past research reporting that translanguaging was supportively manipulated in the manifestation of L1 language input as reading and discussing while processing L2 language output as writing, which moved students to transcend and go beyond the two languages in a critical and creative process (Baker, 2011;Bolkvadze, 2023;Cenoz & Gorter, 2022;Garcia, 2009;Treffers-Daller et al, 2020;Wei, 2011;Yüzlü, & Dikilitaş, 2022a). As Yüzlü and Dikilitaş (2022b) observed that "Translanguaging can serve different purposesmaking meaning, facilitating learning, promoting communicative abilities" (p.186) supported by the assumption that "the boundaries between languages are soft and fluent and that students should benefit from being multilingual by using resources from their whole linguistic repertoire" (Cenoz & Gorter, 2022, p.344).…”
Section: Methodsmentioning
confidence: 96%